The effect of CSR beliefs among bank customers during difficult economic times - Peña-García, Nathalie; Losada-Otálora, Mauricio; ter Horst, Enrique (Frontiers in Communication, 2025)
PurposeThis study investigates how customers perceive corporate social responsibility (CSR) efforts by banks during times of crisis, particularly following the COVID-19 pandemic. It focuses on the authenticity and alignment of CSR actions with customer values and examines how these perceptions influence trust, commitment, and attitudes toward banks.Design/methodologyData were collected from banking customers in the United States, Spain, Mexico, Brazil, and Argentina who were aware of CSR initiatives by their banks. Bayesian statistics and linear regressions were used to analyze the significance of the relationships within the proposed model, providing a robust evaluation of CSR impacts as perceived by customers.FindingsThe study finds that functional CSR initiatives, such as lowering credit card interest rates and offering financial advice, influence CSR beliefs most during economic crises. These findings suggest that during challenging times, customers prioritize practical support over the more abstract CSR initiatives that are often effective in stable conditions.Research limitations/implicationsThe sample was limited to customers aware of CSR initiatives, which may not fully represent the broader population. Additionally, the study captures a specific moment of economic crisis, and future research should assess whether these dynamics persist in different contexts or during more stable economic conditions.OriginalityThis research is unique in providing insights into CSR perceptions during an economic crisis, diverging from prior studies focusing on stable environments. Analyzing specific bank initiatives offers a deeper understanding of how practical CSR efforts resonate with customers during financial distress, contributing valuable knowledge to the fields of CSR and consumer behavior.